Laparoscopic cloasure of Duodenal ulcer perforation - Anang Pangeni (Society of Surgeons of Nepal, 2016)
Introduction and Objective: Duodenal ulcer perforation creates a peritonitis which is sometimes hard to manage, especially with minimally invasive approach. This study is about laparoscopic approach to peritonitis due to duodenal ulcer perforation.